2022
DOI: 10.3389/fendo.2022.959487
|View full text |Cite
|
Sign up to set email alerts
|

The gene regulatory role of non-coding RNAs in non-obstructive azoospermia

Abstract: Non-coding RNAs are classified as small non-coding RNAs, long non-coding RNAs and circular RNAs, which are involved in a variety of biological processes, including cell differentiation, proliferation, apoptosis and pathological conditions of various diseases. Many studies have shown that non-coding RNAs are related to spermatogenesis, maturation, apoptosis, function, etc. In addition, the expression of non-coding RNAs in testicular tissue and semen of patients with non-obstructive azoospermia was different. Ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 98 publications
(96 reference statements)
0
3
0
Order By: Relevance
“…The common causes of NOA include congenital chromosomal abnormalities, gene mutations, and varicocele, but the specific pathogenesis of NOA remains unknown ( Peña et al, 2020 ). A previous study found that lncRNA participates in the progression of NOA ( Zhou et al, 2022 ). LINC00467 upregulated the expression levels of genes related to spermatogenesis ( TDRD6 and LRGUK ) to promote the progression of NOA ( Bo et al, 2020 ).…”
Section: Reproductive Function Diseases Potentially Related To Lncrna...mentioning
confidence: 99%
“…The common causes of NOA include congenital chromosomal abnormalities, gene mutations, and varicocele, but the specific pathogenesis of NOA remains unknown ( Peña et al, 2020 ). A previous study found that lncRNA participates in the progression of NOA ( Zhou et al, 2022 ). LINC00467 upregulated the expression levels of genes related to spermatogenesis ( TDRD6 and LRGUK ) to promote the progression of NOA ( Bo et al, 2020 ).…”
Section: Reproductive Function Diseases Potentially Related To Lncrna...mentioning
confidence: 99%
“…The speci c mechanisms by which lncRNAs regulate miRNAs include: acting as potential pri-miRNAs to generate mature miRNAs, indirectly regulating target gene expression [44]; indirectly inhibiting miRNA-mediated negative regulation of target genes by competitively binding to the 3'-UTR of miRNA target mRNAs [45]; and serving as a "miRNA sponge" to inhibit miRNA expression [46]. On one hand, miRNAs can bind to the 3'-UTR region of lncRNAs, thereby reducing the stability and expression of lncRNAs [47]. On the other hand, miRNAs can return to the cell nucleus and regulate the transcription of lncRNAs, enhancing lncRNA expression.…”
Section: Disscussionmentioning
confidence: 99%
“…MiRNAs as a class of small ncRNAs play a crucial role in downregulating gene expression by competitively interacting with the mRNA 3′UTR region and mediating RNA degradation through the RISC complex ( Zhou et al, 2022 ). MiRNAs have two main applications.…”
mentioning
confidence: 99%